Genetic evaluation of a flock of breeding guinea pigs of Peru genotype - Meza R., Elmer (2017)
This study aimed to genetically evaluate part of the breeding population of guinea pigs, Peru genotype, of the Experimental Station of Instituto Nacional de Innovación Agraria, Ayacucho, Peru, for two parameters: body weight at slaughter (WL) and growth rate (SG). Productive data of of the animals and their family members were collected (n=162 animals), plus environmental factors such as sex, type of birth, month of birth and parturition weight of the mother. The statistical significance on the studied variables was conducted by a fixed effects model. The estimation of breeding values of the offspring wad done by the animal model-BLUP unicharacter. The model included fixed effects that had statistical significance plus the derivative random effects of animal genetic factors. The components of (co) variance included in the model and computational algorithms were solved using the software VCE4 v. 4.2, and PEST v. 4.0, respectively. The estimated breeding values for WL and SG ranged from -84.56 to 79.28 g and from 1.39 to -1.26 g/day, while their levels of accuracy ranged from 28.81 to 89.37%, and 28.46 to 88.35% respectively. The high dispersion of breeding values of the offspring and the high genetic correlation between the traits allow the identification of animals of high genetic merit, and making possible their selection as parents for the next generation.